Price and Income Elasticity of Australian Retail Finance: An Autoregressive Distributed Lag (ARDL) Approach - Helen Higgs; Andrew C. Worthington (Australasian Accounting, Business and Finance Journal, 2014)
This paper models the price and income elasticity of retail finance in Australia using aggregate quarterly data and an autoregressive distributed lag (ARDL) approach. We particularly focus on the impact of the global financial crisis (GFC) from 2007 onwards on retail finance demand and analyse four submarkets (period analysed in brackets): owneroccupied housing loans (Sep 1985–June 2010), term loans (for motor vehicles, household goods and debt consolidation, etc.) (Dec 1988–Jun 2010), credit card loans (Mar 1990–Jun 2010), and margin loans (Sep 2000–Jun 2010). Other than the indicator lending rates and annual full-time earnings respectively used as proxies for the price and income effects, we specify a large number of other variables as demand factors, particularly reflecting the value of the asset for which retail finance demand is derived. These variously include the yield on indexed bonds as a proxy for inflation expectations, median housing prices, consumer sentiment indices as measures of consumer confidence, motor vehicle and retail trade sales, housing debt-to-housing assets as a measure of leverage, the proportion of protected margin lending, the available credit limit on credit cards, and the All Ordinaries Index. In the long run, we find significant price elasticities only for term loans and margin loans, and significant income elasticities of demand for housing loans, term loans and margin loans. We also find that the GFC only significantly affected the long-run demand for term loans and margin loans. In the short run, we find that the GFC has had a significant effect on the price elasticity of demand for term loans and margin loans. Expected inflation is also a key factor affecting retail finance demand. Overall, most of the submarkets in the analysis indicate that retail finance demand is certainly price inelastic but more income elastic than conventionally thought.
Keywords: Retail finance demand; housing loans; term loans; credit card loans; margin loans